Gradient strengthening preparation method of cast high-entropy alloy composite material based on laser cladding preform

By combining laser cladding preforms and vacuum infiltration casting with surface gradient reconstruction, the problems of uneven distribution of reinforcing phases, weak interfacial bonding, and large-size fabrication in high-entropy alloy composites were solved, realizing the gradient nanostructure design of the material and improving its overall performance.

CN121451176APending Publication Date: 2026-02-03JIANGSU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511487341.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-17
Publication Date
2026-02-03

AI Technical Summary

Technical Problem

Existing technologies struggle to achieve uniform distribution of reinforcing phases, low interfacial bonding strength, large-size fabrication, and the construction of performance gradient structures in high-entropy alloy composites. This results in insufficient matching of material strength and toughness, making it impossible to simultaneously meet the requirements of high surface hardness and high core toughness.

Method used

A method combining laser cladding preforms with vacuum infiltration casting and surface gradient reconstruction was adopted. Uniform composite powder was prepared by plasma-assisted ball milling to construct a preform with a gradient pore structure. The gradient nanostructure design of the material was realized by combining three-stage heating infiltration, ultrasonic-assisted laser surface reconstruction and small deformation heat treatment.

Benefits of technology

Large-size, high-performance high-entropy alloy composite materials were successfully prepared, with a surface hardness ≥12 GPa and a core hardness ≥8 GPa. They exhibit excellent high-temperature oxidation resistance and significantly improve the overall performance of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
Patent Text Reader

Abstract

The invention discloses a gradient strengthening preparation method of a cast high-entropy alloy composite material based on a laser cladding preform, and belongs to the technical field of metal matrix composite material preparation. The method comprises the following steps: firstly, preparing composite powder of a high-entropy alloy and a nano ceramic reinforced phase by combining plasma-assisted ball milling with a pulse electromagnetic field; then constructing a prefabricated body with a gradient pore structure by adopting an intelligent regulation and control laser cladding technology; the prefabricated body and a congruent-component high-entropy alloy cast ingot are innovatively metallurgically bonded through a vacuum gradient infiltration process, and a large-size overall composite material is prepared; and finally, forming a gradient nanostructure on the surface layer of the material through ultrasonic-assisted laser surface reconstruction and small-deformation gradient heat treatment. According to the method, the technical problems that reinforcing phases are uneven in distribution, the interface bonding strength is low, and large-size components are difficult to prepare are successfully solved, the prepared composite material has the excellent gradient performance that the surface hardness is larger than or equal to 12 GPa, and the core hardness is larger than or equal to 8 GPa, ceramic particles are evenly distributed in a three-dimensional network shape, the 800-DEG C high-temperature oxidation resistance is improved by 30% or above compared with a traditional high-entropy alloy, and the composite material is suitable for large-size components. The method is particularly suitable for manufacturing high-performance key components in the fields of aerospace, national defense and military industry and the like.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of metal material processing and composite material preparation, and particularly relates to a casting high-entropy alloy composite material gradient strengthening preparation method based on laser cladding preform. BACKGROUND

[0002] High-entropy alloy-based composite materials have broad application prospects in the fields of aerospace, national defense and military industry, etc. due to their excellent high-temperature strength, wear resistance and oxidation resistance. However, the existing preparation technologies have many limitations. First, when a composite material is prepared by a traditional casting method, the reinforcing phase (such as ceramic particles) is prone to segregation and agglomeration, and it is difficult to achieve uniform distribution, and the interface bonding strength with the matrix is low, which seriously restricts the strength and toughness matching of the material. Second, although the powder metallurgy method can improve the distribution of the reinforcing phase, the densification process requires high temperature and high pressure, which is energy-consuming and prone to degradation of the reinforcing phase or interface reaction, making it difficult to prepare large-size and complex-shaped components. Third, the laser cladding technology is often used to prepare surface composite material coatings, but the single-track cladding thickness is limited, the bonding mode with the matrix is metallurgical bonding, and it is difficult to prepare an overall composite material, and there are problems such as composition segregation and non-uniform structure. More importantly, the existing technologies are difficult to construct a reasonable performance gradient structure in the material. Most of the materials prepared by the methods are either overall strengthened (resulting in decreased toughness) or only surface coatings (not matching the performance of the matrix), which cannot achieve continuous gradient performance distribution from the surface to the core, that is, it cannot meet the requirements of high hardness, high wear resistance on the surface and high toughness in the core at the same time. SUMMARY

[0003] In view of the deficiencies in the prior art, the application provides a casting high-entropy alloy composite material gradient strengthening preparation method based on laser cladding preform. The core innovation of the application is that a composite preparation route of "laser cladding preform + vacuum infiltration casting + surface gradient reconstruction" is adopted, which skillfully solves the problems of uniform distribution of reinforcing phase, interface bonding control and large-size preparation, and successfully realizes the gradient performance design of the material from the surface to the core.

[0004] The application first provides a casting high-entropy alloy composite material gradient strengthening preparation method based on laser cladding preform, characterized in that it comprises the following steps: (1) Composite powder preparation: high-entropy alloy powder (particle size 10-45 μm) and nano-ceramic reinforcing phase (particle size 20-150 nm) prepared by vacuum induction melting and gas atomization are plasma-assisted ball milled at a mass ratio of 75:25 to 90:10, the ball milling parameters are as follows: ball-to-material ratio 8:1-12:1, rotation speed 250-450 rpm, time 3-8 h, argon gas is introduced during the process, and a pulsed electromagnetic field (frequency 5-10 Hz, strength 0.3-0.8 T) is applied intermittently; (2) Laser cladding forming: using coaxial powder feeding type laser cladding system, setting laser power 1000-1800 W, spot diameter 0.8-1.5 mm, scanning speed 4-12 mm / s, overlap rate 25-45%, under helium protection, multi-layer and multi-pass cladding, interlayer temperature control at 150-250 ℃, to obtain the preform with gradient porous structure; (3) Vacuum gradient infiltration: placing the preform in the directional solidification furnace with the same composition high-entropy alloy ingot at the bottom, using three-stage heating system: the first stage is to rise to 1200 ℃ at 10-15 ℃ / min and keep for 30 min, the second stage is to rise to 1500-1550 ℃ at 5-8 ℃ / min and keep for 60-90 min, the third stage is to cool to 1000 ℃ quickly and then cool with the furnace, the whole process is under vacuum degree ≤5×10-3 Pa; (4) Ultrasonic assisted laser surface reconstruction: using pulsed laser (frequency 15-40 kHz, pulse width 2-8 ms) combined with 28-45 kHz ultrasonic vibration field to selectively remelt the surface of the blank, ultrasonic power density 0.3-0.8 W / mm 2 , laser-ultrasonic action area overlap rate 60-80%; (5) Small deformation gradient heat treatment: first multi-directional micro-rolling at 850-950 ℃ (single pass deformation 3-8%, total deformation 15-25%), then two-stage aging treatment: the first stage is to keep at 500-550 ℃ for 2-4 h, the second stage is to keep at 600-650 ℃ for 1-2 h, finally obtaining the surface strengthening layer with gradient nanostructure.

[0005] Further, in step (1), the high-entropy alloy is at least one selected from FeCoNiCrAl, TiZrNbHfTa or CoCrFeMnNi system, and the ceramic reinforcing phase is TiB2, SiC, YN or their core-shell structure composite particles.

[0006] Further, the laser cladding of step (2) adopts an intelligent parameter control strategy, including: adjusting the laser power (±10% dynamic adjustment) according to the real-time feedback of infrared thermal imaging, using a spiral progressive scanning path, and inserting an annealing layer with 50% power every 3 layers.

[0007] Further, the infiltration process of step (3) applies an axial static magnetic field of 0.5-1.2 T, and an isostatic pressure of 10-20 MPa is applied during the cooling stage.

[0008] Further, in the ultrasonic assisted laser treatment of step (4), the amplitude focusing ultrasonic and the laser beam form an angle of 30-60 °, and intermittent ultrasonic (working period 2-4 s, interval 1-2 s) is applied.

[0009] Further, step (5) after the small deformation heat treatment also includes: surface laser shock peening (energy density 5-8 J / cm 2 , impact 3-5 times), low-temperature ion nitriding treatment (temperature 350-400 DEG C, time 4-6 h).

[0010] The application also provides a high-entropy alloy composite material prepared by the above method, characterized by having: surface hardness >= 12 GPa, core hardness >= 8 GPa, three-dimensional network distribution of ceramic particles (spacing 100-300 nm), surface layer grain size 50-150 nm, transition layer 200-500 nm, matrix 1-3 microns, and 800 DEG C high-temperature oxidation resistance superior to traditional high-entropy alloys by more than 30%.

[0011] Compared with the prior art, the application has the following beneficial effects: (1) Preform innovation construction: uniform distribution of composite powder is prepared by plasma-assisted ball milling combined with pulsed electromagnetic field, and an intelligent controlled laser cladding technology is used to construct a preform with a gradient porosity structure. This method not only ensures the uniform distribution of the reinforcing phase, but also provides an optimized channel for the subsequent infiltration process through the gradient porosity design.

[0012] (2) Large size preparation breakthrough: innovatively combine the preform prepared by laser cladding with vacuum infiltration casting technology. Through a three-stage gradient heating infiltration process, the preform and the matrix ingot are metallurgically combined, and a large-size, integrated composite material component is successfully prepared, breaking through the limitation of traditional laser cladding which can only prepare coatings.

[0013] (3) Surface gradient strengthening innovation: a new method combining ultrasonic-assisted laser surface reconstruction with small deformation gradient heat treatment. The introduction of cavitation effect and acoustic streaming effect in the ultrasonic field significantly improves the mass transfer and solidification behavior of the laser remelting process. Small deformation multi-directional rolling combined with two-stage aging treatment successfully constructs a gradient nanostructure in the surface layer, achieving perfect matching of surface hardness (>= 12 GPa) and core toughness (hardness >= 8 GPa).

[0014] (4) Process synergy optimization: an organic whole is formed between each step: the gradient porosity structure of the preform provides a channel for infiltration; the three-stage heating schedule of the infiltration process ensures the interface bonding quality; the synergistic effect of surface remelting and small deformation heat treatment realizes gradient nanostructure regulation. This multi-process synergy innovation ensures that the final material has a three-dimensional network distribution of reinforcing phases (spacing 100-300 nm) and a gradient grain structure from the surface layer (50-150 nm) to the matrix (1-3 microns), as well as excellent high-temperature oxidation resistance (superior to traditional high-entropy alloys by more than 30%). BRIEF DESCRIPTION OF DRAWINGS

[0015] Figure 1 Microstructure of the composite material obtained in Example 1 of the present application. DETAILED DESCRIPTION

[0016] The present application will be further described in conjunction with the accompanying drawings and specific examples, but the embodiments of the present application are not limited thereto. Example 1

[0017] A high-entropy alloy composite material is prepared with FeCoNiCrAl-based high-entropy alloy as the matrix and TiB2 as the reinforcing phase.

[0018] (1) Composite powder preparation: Plasma-assisted ball milling is performed on vacuum induction melted gas atomized FeCoNiCrAl high-entropy alloy powder (particle size 10-45 μm) and nano-TiB2 ceramic particles (particle size 50-100 nm) in a mass ratio of 85:15. The ball milling parameters are: ball-to-material ratio 10:1, rotation speed 350 rpm, time 5 h, argon gas protection is applied during the process and a pulsed electromagnetic field (frequency 8 Hz, intensity 0.5 T) is applied intermittently.

[0019] (2) Laser cladding forming: A coaxial powder feeding type laser cladding system is used, with laser power set at 1500 W, spot diameter 1.2 mm, scanning speed 8 mm / s, and overlap rate 35%. Multi-layer and multi-pass cladding is performed under helium gas protection, with the interlayer temperature controlled at 200 ℃. An intelligent parameter control strategy is adopted, with the laser power adjusted in real time according to the feedback from infrared thermal imaging. A spiral progressive scanning path is adopted, with an annealing treatment layer of 50% power inserted every 3 layers to obtain a preform with gradient porosity structure.

[0020] (3) Vacuum gradient infiltration: The preform is placed in a directional solidification furnace with a high-entropy alloy ingot of the same composition at the bottom. A three-stage temperature rising system is used: the first stage rises to 1200 ℃ at a rate of 12 ℃ / min and maintains for 30 min, the second stage rises to 1520 ℃ at a rate of 6 ℃ / min and maintains for 75 min, and the third stage is rapidly cooled to 1000 ℃ and then cooled with the furnace. An axial static magnetic field of 0.8 T is applied during the infiltration process, and an isostatic pressure of 15 MPa is applied during the cooling stage. The vacuum degree is maintained at ≤5×10 -3 Pa throughout the process.

[0021] (4) Ultrasonic-assisted laser surface reconstruction: Pulsed laser (frequency 30 kHz, pulse width 5 ms) is used to cooperate with a 35 kHz ultrasonic vibration field to selectively remelt the surface of the blank. The ultrasonic power density is 0.5 W / mm 2 , and the overlap rate of the laser-ultrasonic action area is 70%. The amplitude focusing ultrasonic and laser beam are at an angle of 45°, and intermittent ultrasonic (working period 3 s, interval 1.5 s) is applied.

[0022] (5) Small deformation gradient heat treatment: first multi-directional micro-rolling at 900 ℃ (single pass deformation 5%, total deformation 20%), followed by two-stage aging treatment: first stage 520 ℃ for 3 h, second stage 620 ℃ for 1.5 h, and finally surface laser shock peening (energy density 6 J / cm 2 , impact 4 times) and low-temperature ion nitriding treatment (temperature 380℃, time 5h) to obtain a surface strengthening layer with gradient nanostructure.

[0023] The prepared high-entropy alloy composite material is tested for performance: the surface hardness reaches 12.5 GPa, the core hardness is 8.3 GPa, the ceramic particles are uniformly distributed in a three-dimensional network, as shown in Figure 1 , the surface layer grain size is 80-120 nm, the transition layer is 300-400 nm, and the matrix is 1.5-2.5 μm, and the high-temperature oxidation resistance at 800℃ is increased by 35% compared with traditional FeCoNiCrAl high-entropy alloy.

[0024] Comparative Example 1 A high-entropy alloy composite material with the same composition is prepared by a traditional powder metallurgy method: high-entropy alloy powder and TiB2 powder are mechanically mixed and then hot isostatic pressed and sintered.

[0025] The results show that the distribution of the reinforcing phase is uneven, and there is a significant agglomeration phenomenon. The hardness distribution of the material is uneven, there are defects at the interface, the high-temperature oxidation resistance is only increased by 15% compared with the matrix alloy, and the toughness is significantly reduced.

[0026] Comparative Example 2 A composite material coating is prepared on the surface of the matrix by conventional laser cladding technology.

[0027] The results show that the coating and the matrix are metallurgically bonded, but the coating thickness is limited (<2 mm), and there is obvious composition segregation and uneven microstructure, which cannot realize the preparation of large-size whole composite material, and the surface and core performance are not matched. Example 2

[0028] It is basically the same as Example 1, except that: step (1) uses CoCrFeMnNi high-entropy alloy powder and SiC nanoparticles (mass ratio 80:20); step (3) adjusts the melting temperature to 1500℃; step (5) adjusts the micro-rolling temperature to 850℃. The surface hardness of the final composite material is 12.3 GPa, the core hardness is 8.2 GPa, and the 800℃ oxidation resistance is increased by 32%. Example 3

[0029] The same as example 1, except that: step (1) uses TiZrNbHfTa high-entropy alloy powder and YN nanoparticles (mass ratio 90:10); step (3) applies a 1.0T static magnetic field during infiltration; and step (5) increases the number of laser shock peening to 5 times. The surface hardness of the finally obtained composite material reaches 13.2GPa, the core hardness is 8.8GPa, and the 800℃ oxidation resistance is increased by 38%.

[0030] The above example results show that the high-entropy alloy composite material prepared by the present application has excellent comprehensive performance and obvious gradient characteristics, fully proving the effectiveness and superiority of the method of the present application.

[0031] The above examples are preferred embodiments of the present application, but the present application is not limited to the above embodiments, and any obvious improvements, replacements or modifications made by those skilled in the art without departing from the essential content of the present application shall fall within the protection scope of the present application.

Claims

1. A method for preparing cast high-entropy alloy composite materials based on laser cladding preforms with gradient strengthening, characterized in that, Includes the following steps: (1) Preparation of composite powder: High-entropy alloy powder (particle size 10-45 μm) atomized by vacuum induction melting and nano-ceramic reinforcing phase (particle size 20-150 nm) were subjected to plasma-assisted ball milling at a mass ratio of 75:25 to 90:

10. The ball milling parameters were: ball-to-material ratio 8:1-12:1, rotation speed 250-450 rpm, time 3-8 h. Argon gas was introduced for protection during the process and pulsed electromagnetic field (frequency 5-10 Hz, intensity 0.3-0.8 T) was applied intermittently. (2) Laser cladding forming: A coaxial powder feeding laser cladding system is adopted, with a laser power of 1000-1800 W, a spot diameter of 0.8-1.5 mm, a scanning speed of 4-12 mm / s, and an overlap rate of 25-45%. Multi-layer and multi-pass cladding is carried out under helium protection, and the interlayer temperature is controlled at 150-250 ℃ to obtain a preform with a gradient pore structure. (3) Vacuum gradient infiltration: The preform is placed in a directional solidification furnace with a high-entropy alloy ingot of the same composition at the bottom. A three-stage heating regime is adopted: the first stage is heated to 1200 ℃ at 10-15 ℃ / min and held for 30 min; the second stage is heated to 1500-1550 ℃ at 5-8 ℃ / min and held for 60-90 min; the third stage is rapidly cooled to 1000 ℃ and then cooled with the furnace. The vacuum degree throughout the process is ≤5×10 -3 Pa; (4) Ultrasonic-assisted laser surface reconstruction: Pulsed laser (frequency 15-40 kHz, pulse width 2-8 ms) combined with an ultrasonic vibration field of 28-45 kHz is used to selectively remelt the surface of the billet. The ultrasonic power density is 0.3-0.8 W / mm². 2 The overlap rate of the laser-ultrasound interaction area is 60-80%. (5) Small deformation gradient heat treatment: First, multi-directional micro-rolling is carried out at 850-950 ℃ (single-pass deformation amount 3-8%, total deformation amount 15-25%), followed by two-stage aging treatment: the first stage is held at 500-550 ℃ for 2-4 h, and the second stage is held at 600-650 ℃ for 1-2 h, finally obtaining a surface strengthening layer with gradient nanostructure.

2. The method according to claim 1, characterized in that: The high-entropy alloy in step (1) is at least one selected from FeCoNiCrAl, TiZrNbHfTa or CoCrFeMnNi system, and the ceramic reinforcing phase is TiB2, SiC, YN or their core-shell structure composite particles.

3. The method according to claim 1, characterized in that: The laser cladding in step (2) adopts an intelligent parameter control strategy, including: adjusting the laser power (±10% dynamic adjustment) based on real-time feedback from infrared thermal imaging. A spiral progressive scanning path is adopted, and an annealing layer with 50% power is inserted every 3 layers.

4. The method according to claim 1, characterized in that: In step (3), an axial static magnetic field of 0.5-1.2 T is applied during the melting and infiltration process, and an isostatic pressure of 10-20 MPa is applied during the cooling stage.

5. The method according to claim 1, characterized in that: In step (4) of ultrasound-assisted laser processing, a variable amplitude rod is used to focus the ultrasound at an angle of 30-60° to the laser beam, and intermittent ultrasound is applied (working cycle 2-4 s, interval 1-2 s).

6. The method according to claim 1, characterized in that: Step (5) after the small deformation heat treatment also includes: surface laser shock strengthening (energy density 5-8 J / cm²). 2 (Impact 3-5 times), low-temperature ion nitriding treatment (temperature 350-400 ℃, time 4-6 h).

7. A high-entropy alloy composite material prepared by any one of claims 1-6, characterized in that... It has the following characteristics: surface hardness ≥12 GPa, core hardness ≥8 GPa, and ceramic particles distributed in a three-dimensional network (spacing 100-300 nm). The surface grain size is 50-150 nm, the transition layer is 200-500 nm, and the matrix is ​​1-3 μm. Its high-temperature oxidation resistance at 800 ℃ is more than 30% better than that of traditional high-entropy alloys.